Sweet Potato Is Not Simply an Abundant Food Crop: A Comprehensive Review of Its Phytochemical Constituents, Biological Activities, and the Effects of Processing - Emily P. Laveriano-Santos; Anallely López-Yerena; Carolina Jaime-Rodríguez; Johana González-Coria; Rosa M. Lamuela-Raventós; Anna Vallverdú-Queralt; Joan Romanyà; Maria Pérez (MDPI AG, 2022)
Nowadays, sweet potato (Ipomoea batata L.; Lam.) is considered a very interesting nutritive food because it is rich in complex carbohydrates, but as a tubercle, contains high amounts of health-promoting secondary metabolites. The aim of this review is to summarize the most recently published information on this root vegetable, focusing on its bioactive phytochemical constituents, potential effects on health, and the impact of processing technologies. Sweet potato is considered an excellent source of dietary carotenoids, and polysaccharides, whose health benefits include antioxidant, anti-inflammatory and hepatoprotective activity, cardiovascular protection, anticancer properties and improvement in neurological and memory capacity, metabolic disorders, and intestinal barrier function. Moreover, the purple sweet potato, due to its high anthocyanin content, represents a unique food option for consumers, as well as a potential source of functional ingredients for healthy food products. In this context, the effects of commercial processing and domestic cooking techniques on sweet potato bioactive compounds require further study to understand how to minimize their loss.